GAMBARAN KECEMASAN DAN SIKLUS MENSTRUASI PADA MAHASISWI TINGKAT AKHIR DI FAKULTAS KEPERAWATAN UNRI - Puput Putriyani; Herlina Herlina; Wasisto Utomo (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Anxiety often occurs in students, psychosocial stressors are one of the triggers for anxiety in students, anxiety causes systemic changes in the body, this makes menstruation in women last a long time so that the cumulative amount of blood that comes out can cause anemia. The purpose of this study was to describe the anxiety of the menstrual cycle in final year female students at the Faculty of Nursing, UNRI. Methods: This study used a quantitative descriptive research design using univariate analysis. The sample in this study was 132 respondents, namely final year A 2018 students at the Faculty of Nursing, University of Riau based on inclusion criteria using a total sampling technique. Results: The results showed that the normal level of anxiety was 96 respondents (72.7%) and mild anxiety was 35 respondents (26.5%). Menstrual cycles in female students are categorized as normal, amounting to 106 respondents (80.3). Conclusion: Anxiety in female students of the Faculty of Nursing, University of Riau is in the normal category, and female menstrual cycles are normal. This research is expected to be a reference material for institutions related to the characteristics of anxiety and the menstrual cycle.